Integrity In Dietrich Bonhoeffer’s Christian Ethical Analysis Of Deviations In The Implementation Of Congregational Council Decisions - Christian Gabriel Sumajow; Hendry Corneles Mamengko Runtuwene (International Journal of Education, Information Technology, and Others, 2026)
This study analyzes deviations in the implementation of decisions made by the Church Council in churches using the lens of Dietrich Bonhoeffer’s Christian ethics. This study uses a qualitative research method with a descriptive approach. The study was conducted at the Victory Tompasobaru GMIM Congregation, where discrepancies were found between the decisions of the council and their implementation, caused by weak leadership integrity and accountability. Using descriptive qualitative methods, the study examined the dynamics of church leadership, the presbyterial-synodal system, and the decision-making process. Bonhoeffer’s ethical analysis—particularly the concepts of costly grace, Christus als Wirklichkeit (Christ as reality), and Stellvertretung (primacy/responsibility of representation)—was used to diagnose the root causes of these deviations. The results of the study show that deviations in the implementation of decisions are not only procedural violations, but also theological-ethical failures in fulfilling the call to responsible leadership before God and the congregation. As a solution, the study offers a holistic reconstruction that includes spiritual nurturing, strengthening accountability structures, and developing a culture of openness in church assemblies, so that the integrity and credibility of church leadership can be restored.